Pattern of Skin Diseases among Patients Attending Military Hospital, Ramu (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: The pattern and distribution of skin diseases varies from one country to another and even in different areas within the same country. Skin diseases can be influenced by so many factors like genetics, environment, race, religion, occupation, nutrition and habit. Skin diseases affect all ages from neonate to elderly.Objectives: To evaluate the pattern of skin diseases in patients attending outpatient department (OPD) at military hospital, Ramu.Materials and Methods: This cross-sectional observational study was conducted in CMH, Ramu from July to December 2019 among 1700 patients. All newly diagnosed patients of skin diseases irrespective of age and sex attended the OPD of the hospital were selected by purposive sampling. Patients’ diagnosis was made clinically by a dermatologist and lab investigations were performed only in case of diagnostic importance.Results: Mean age of patients was 27.1±12.7 years and 58.8% were male. Majority (96.5%) received formal education and 59.4% were married. The mean of the numbers of family members of the respondents was 4.0±1.0. Maximum 36.5% respondents suffered from eczema followed by superficial fungal infection 19.5%, scabies 14.1%, acne vulgaris 11.2%, psoriasis 3.5% and viral warts 2.9%. Scabies was higher among younger age group and acne vulgaris was higher among females and these association was statistically significant (p < .05).Conclusion: By appropriate prevention and awareness program morbidity associated with few contagious skin diseases can be reduced and a good amount of money and manpower can be saved.JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 51-53